Effects of Electromyostımulatıon Traınıng on Body Composıtıon - İlkay Doğan; Mehmet Kirişçioğlu; Mürsel Biçer; Zarife Pancar (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to examine the variables such as weight, body fat percentage and amount, lean body mass (FFM) and body mass index (BMI) occurred on body as a result of realization of voluntary contraction and involuntary contraction together with training by electromyostimulation (EMS) system. 41 voluntary women joined the study as treatment (n=20) and control group (n=21). a 25-minute training program was arranged for treatment group with Bodytec EMS device twice a week for 8 weeks. Training was done as strength and durability exercises for 12 minutes, cardio exercises for 8 minutes and active rest for 5 minutes. Ages, genders, lengths, weights, fat percentages, lean body masses and body mass indexes of groups were measured both whole and regional, and then these parameters were compared before and after treatment. Measurements were donetwice as pre-test and post-test. Tanita bc 418 body analyzer belongs to Bio Electricity Impedans method was used for all measurements. In data analysis, 2*2 Repeated Measures Varians Analysis (Repeated Measures ANOVA) was used to compare pre-test and post-test measures.Statistical results were evaluated at p˂.05 significance level. Consequently, p˂.05 significance level was identified in favor of the post-tests analyzes of pre-tests and last tests of experimental group in body weight , BMI , fat % (body fat ratio) ,values of fat mass (amount of fat), value of right foot fat percent , value of right foot fat mass , value of left foot fat percent , value of left foot fat mass ,body fat mass in value of right-left arms fat percent. Statistically, p˂.05 significance level was determined between pre-tests and post-tests of control group's measurements.